Improvement of Functional Planning Organization of Rural Settlements in Suburban Zones - Kuzmenko, Tetiana; Liakh, Vasyl; Dmytrenko, Andrii (International Journal of Engineering and Technology, 2018)
The purpose of the article is to define the principles of functional and planning organization of suburban rural settlements (SRS) and to determine the main techniques corresponding with them.Researches, which were conducted, and analysis of existing experience of formation of settlement planning structure and summarizing research and methodics literature determined allocation of principles of unity with central city, functional specialization, alternativeness and systematics of town-planning documentation updating. The following methods guarantee implementation of them: organic integration of objects of small business and service into the production-residential and production-service formations as new design objects, formation of new town-forming functions of settlements: businesses, services, recreations; formation of different functional types of SRS, considering dependence of plan structure on external transport corridors and natural features; forming SRS with a number of functions: monofunctional, bifunctional, multifunctional; identification of the most suitable way of development of SRS according to the defining factors of development and its gradual formation as certain type, the choice of the defining factors of development and mark assessmentÂ  based on the defining factors of development; transformation of structural parts of the settlement and their re-profiling into a different function. Recommendations for improvement of functional and planning organization of different SRS types have been developed. Â